Intergenerational mentoring for young adult males with intellectual disability: Intervention description and outcomes - Wilson, Nathan J.; Cordier, Reinie; Milbourn, Ben; Mahoney, Natasha; Hoey, C.; Buchanan, Angus (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
Background: Gaining employment can be challenging for young adults with intellectual disability (ID). This study reports on a mentoring intervention to help counter barriers to employment. Method: A single-group, pre-post design was used. Eighteen young men with mild to moderate ID joined a local Men’s Shed and were assigned a Shed member as their mentor. Pre- and post-measures assessed quality of life, loneliness, personal wellbeing and workplace adjustment. Techniques from the Behaviour Change Taxonomy were used to provide support to both mentee and mentor. Results: There was a significant improvement in the community domain of quality of life. There were no significant differences in loneliness, wellbeing or workplace adjustment. Mentees attended more social events independently, and increased skills and community participation. Conclusion: By providing targeted and graded support to the mentee-mentor dyad, community-based interventions can provide a sense of community and develop workplace skills for young people with ID.